Effect of Nitrogen Levels and Gliricidia Sepium Alley Widths on Rice Based Agroforestry Systems (Bangladesh Rice Journal, 2014)
An experiment was conducted at the research farm of Bangabandhu Sheikh Mujibur Rahman Agricultural University (BSMRAU) during May to September 2008 to investigate the effect of alley widths of Gliricidia sepium and different nitrogen levels on yield of Aus rice (BR24). The experiment was laid out in a split-plot design with three replications. Three alley widths 3.0, 4.5, and 6.0 m and a control, without tree were compared under five N doses 0, 18.75, 37.5, 56.25 and 75 kg ha-1. G. Sepium species gave the highest (20.24 t ha-1) pruned materials from closer alley width (3m). The highest grain yield (3.54 t ha-1) of rice was obtained at 75 kg N from urea and pruned materials (PM) in 4.5 m alley width. The study suggests that G. sepium can contribute to increase rice yield and increase N use efficiency.DOI: http://dx.doi.org/10.3329/brj.v17i1-2.20898Bangladesh Rice j. 2013, 17(1&2): 26-32